PENGARUH MANAJEMEN KONFLIK TERHADAP PRODUKTIVITAS AGEN PADA PT. BNI LIFE INSURANCE CABANG PEKANBARU - Gultom, Elida (Sekolah Tinggi Ilmu Ekonomi Riau, 2018)
This study aims to determine the effect of conflict management on the productivity of agents at PT. BNI Life Insurance Pekanbaru Branch. Total population of 63 people with a sample of 63 respondents where the sampling technique using premises using census samples The method of collecting data using a questionnaire. The data analysis technique used is simple linear regression with SPSS 17 for Windows tool. The results show that there is a significant effect of conflict management on agent productivity. Based on the results of analysis, it is known that t count> t table (6.029> 2.000) with probability (0.00 <0.05) So for the variable conflict management partially significant effect on agent productivity This means Ho accepted and reject Ha.From the test results determination , Contribution of conflict management variable (X) influence agent productivity variable (Y) equal to 37,3% and balance 62,7% influenced by other variable not examined in this research.Recommendations given to improve the productivity of agents is the leader should not borednya give motivation and passion to the agent